ELECTRICAL STUNNING AND PRE-SLAUGHTERING TIME INTERVAL EFFECT IN EXPRESSION OF HEART BROILER CHICKENS PROTEIN - Hermanto, Sandra (Fakultas Farmasi, Universitas Gadjah Mada, 2015)
Pre-slaughtering process by transporting broiler chickens from farm to slaughterhouse and treatment of electrical stunning could be one of halal critical point. Stressing on chickens could be trigger a specific protein expression or increase its expression as a result of changes in metabolism that occurs. The purpose of this study was to identify the effect of treatment of electrical stunning and the pre-slaughtering interval time on broiler chicken liver protein expression through the analysis of protein profile by SDS-PAGE. Experiments conducted on 7 broiler chickens aged 35 days were given pre-slaughter treatment are different. Treatments include electrical stunning of 0 V, 25 V and 250 V as well as the pre-slaughtering time interval 0 hours, 2 hours, 2 hours + 12 hours (fasting) and 2 hours + 12 (fasting) with electrical stunning 250 V. Each of samples (chicken liver protein) isolated by homogenized in Trs-HCl buffer and the protein concentration determined by Lowry method. Identification of the protein profile was done by observing the differences in the intensity of the electrophoresis results followed by densitometry analysis. The results showed significant differences in outcomes electrical stunning treatment as indicated by the appearance of protein bands at around 109 kDa and do not appear on other treatments. The difference is predicted from particular protein expressed induced by cell metabolism responsive in chicken liver cell.